Earning more from wild mushrooms - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Meg Faville, a Peace Corps volunteer, describes how a group of women have learned to improve their mushroom handling and marketing, and become more self-reliant.